Pengaruh Jumlah Konsentrasi Kalsium Klorida (CACL2) Terhadap Kualitas Virgin Coconut Oil (VCO) - Anna Dhora (Politeknik Kampar, 2019)
Virgin coconut oil (VCO) is a product from coconut that given mechanical treatment without heating process and without changing the original nature of the oil. Some methods were often applied in the manufacture of VCO such as fermentation, centrifugation method, acidification methods, and salting method. In salting method, salt (eq. CaCl2) would be added. The aim of salting methode was to break the coconut milk emulsion system by setting the solubility of proteins in saline . Salt was used to break of emulsion stability . The result of research was concluded that the length of times 2 days is more effective when compared to 3 days. The values ??obtained were: yield 38.83 %, ALB 0.29 % and the water content was 0.02 % . For organoleptic test, it was concluded that the panelists preferred the VCO produced on 2 days, because its producing a distinctive flavor and fresh coconut aroma and color was crystal clear.